How are global health policies transferred to sub-Saharan Africa countries? A systematic critical review of literature - Walter Denis Odoch; Flavia Senkubuge; Ann Bosibori Masese; Charles Hongoro (BMC, 2022)
Abstract Background Most sub-Saharan Africa countries adopt global health policies. However, mechanisms with which policy transfers occur have largely been studied amongst developed countries and much less in low- and middle- income countries. The current review sought to contribute to literature in this area by exploring how health policy agendas have been transferred from global to national level in sub-Saharan Africa. This is particularly important in the Sustainable Development Goals (SDGs) era as there are many policy prepositions by global actors to be transferred to national level for example the World Health Organization (WHO) policy principles of health financing reforms that advance Universal Health Coverage (UHC). Methods We conducted a critical review of literature following Arksey and O'Malley framework for conducting reviews. We searched EBSCOhost, ProQuest, PubMed, Scopus, Web of Science and Google scholar for articles. We combined the concepts and synonyms of "policy transfer" with those of "sub-Saharan Africa" using Boolean operators in searching databases. Data were analyzed thematically, and results presented narratively. Results Nine articles satisfied our eligibility criteria. The predominant policy transfer mechanism in the health sector in sub-Saharan Africa is voluntarism. There are cases of coercion, however, even in the face of coercion, there is usually some level of negotiation. Agency, context and nature of the issue are key influencers in policy transfers. The transfer is likely to be smooth if it is mainly technical and changes are within the confines of a given disease programmatic area. Policies with potential implications on bureaucratic and political status quo are more challenging to transfer. Conclusion Policy transfer, irrespective of the mechanism, requires local alignment and appreciation of context by the principal agents, availability of financial resources, a coordination platform and good working relations amongst stakeholders. Potential effects of the policy on the bureaucratic structure and political status are also important during the policy transfer process.